2022
DOI: 10.7759/cureus.27101
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Compression Due to Tophaceous Vertebral Gout: A Case Report

Abstract: Gout tophi are deposits of urate crystals in subcutaneous tissues and joints which commonly affect the small joints of the feet and hands, causing painful arthritis. The axial skeleton is considered to be seldom affected by gout arthritis. Here we describe the clinical, MRI, and pathologic findings of a 61-year-old male patient with a previous diagnosis of gout who presented with progressive paraparesis and radicular pain. MRI showed extradural masses compressing the spinal cord and roots at two spinal levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…For spinal gout, the most affected locations are the lumbar region and sacroiliac joints. In the vertebral column, gout tophi can affect almost every anatomical component, such as vertebral bodies, intervertebral disc, epidural space, articular facets, laminae, ligamentum flavum, pedicles and rarely the intradural space ( 5 ). It was also reported that the lateral parts of the vertebra are much more affected than the central areas ( 6 ); however, the sole infiltration of the intervertebral foramen was never reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For spinal gout, the most affected locations are the lumbar region and sacroiliac joints. In the vertebral column, gout tophi can affect almost every anatomical component, such as vertebral bodies, intervertebral disc, epidural space, articular facets, laminae, ligamentum flavum, pedicles and rarely the intradural space ( 5 ). It was also reported that the lateral parts of the vertebra are much more affected than the central areas ( 6 ); however, the sole infiltration of the intervertebral foramen was never reported.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the present case with lesions of spinal gout tophus in the intervertebral foramen was the first of its kind reported in the literature. The initially reported cases were all massive compressing lesions in the lumbar spinal canal with definite clinical symptoms, such as in the studies by Chen et al ( 3 ), Abreu Casas et al ( 5 ), Ribeiro da Cunha et al ( 7 ), Brahmbhatt et al ( 8 ) and Kim et al ( 15 ). Compared with the previous publications, the MRI appearance reported in the present study was more difficult to differentiate from degenerative spinal disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La goutte chronique tophacée polyarticulaire est le quatrième et ultime stade évolutif de la maladie goutteuse [5]. Le 1er cas de goutte axiale fut décrit en 1950 par Kersley GD sur un cas autopsique de subluxation par érosion tophique de l'Atlas (C1) avec protrusion de l'Odontoïde dans le Foramen Magnum [6,7,8]. Koskoff YD et al décrivait 3 ans plus tard la première myélopathie goutteuse et Reynolds AF Jr en 1976, les 3 premiers cas neurochirurgicaux de goutte rachidienne par tophi flavo-ligamentaires (ligament jaune) compressifs [6], comme retrouvé dans nos 2 cas.…”
Section: Discussionunclassified